Juazeiro do Norte (Ceará, Brazil):: A Case of Urban (In)Sustentability (Sustainability in Debate, 2014)
This paper aims to study the city of Juazeiro do Norte, midsize city of the interior of Ceará; theprospects for urban sustainability in this metropolis. This is a qualitative research, fitting into theexploratory perspective. As methods and research techniques, we opted for the literature review,case studies and field visits. The city of Juazeiro do Norte experiences vigorous economicinvestments and large demographic expansion; however, still needs, urgently, reformulations inseveral segments, aiming to increase the quality of urban life and environmental conservation.We argue that the guiding direction that should govern the pursuit of urban sustainability is thetransformation of the current progress in economic growth guided by a model of developmenttruly sustainable.